2020
DOI: 10.1089/caff.2020.0011
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine and Ketogenic Treatments

Abstract: It is well known that the neuromodulator adenosine, acting through the adenosine A 1 receptor subtype, can limit or stop seizures. In 2008, adenosine was proposed as a key component of the anticonvulsant mechanism of the ketogenic diet (KD), a very low carbohydrate diet that can be highly effective in drug-refractory epilepsy. In this study, we review the accumulated data on the intersection among adenosine, ketosis, and anticonvulsant/antiepileptogenic effects. In several rodent models of epilepsy and seizure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 66 publications
0
11
0
1
Order By: Relevance
“…Thus, these results above suggest that effect of both uridine and KSMCT on absence epileptic activity may be modulated (at least partly) by A 1 Rs. According to this hypothesis, it was demonstrated that A 1 Rs can inhibit epileptic activity [ 1 , 4 , 45 , 58 , 62 ], brain areas, such as somatosensory cortex, which may have a role in absence epilepsy genesis contain A 1 Rs [ 1 , 44 , 45 , 63 ] and activity (expression) of A 1 Rs was decreased in the somatosensory cortex (cortical focus) in presymptomatic WAG/Rij rats [ 1 , 4 , 45 ]. By synaptic inhibition, A 1 Rs, among others, may reduce Ca 2+ influx and inhibits excitatory synaptic transmission (e.g., decreases the release of glutamate) as well as increase the activity of ATP-sensitive potassium channels [ 4 , 60 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, these results above suggest that effect of both uridine and KSMCT on absence epileptic activity may be modulated (at least partly) by A 1 Rs. According to this hypothesis, it was demonstrated that A 1 Rs can inhibit epileptic activity [ 1 , 4 , 45 , 58 , 62 ], brain areas, such as somatosensory cortex, which may have a role in absence epilepsy genesis contain A 1 Rs [ 1 , 44 , 45 , 63 ] and activity (expression) of A 1 Rs was decreased in the somatosensory cortex (cortical focus) in presymptomatic WAG/Rij rats [ 1 , 4 , 45 ]. By synaptic inhibition, A 1 Rs, among others, may reduce Ca 2+ influx and inhibits excitatory synaptic transmission (e.g., decreases the release of glutamate) as well as increase the activity of ATP-sensitive potassium channels [ 4 , 60 , 64 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a ketogenic diet causes the body to utilize ketones instead of glucose for cellular energy, and ketone metabolism produces fewer reactive oxygen species and free radicals than glucose metabolism ( 154 ). Finally, ketone metabolism elevates adenosine ( 155 ), which is known to be anti-inflammatory ( 156 ).…”
Section: Non-pharmacological Treatments For Sci Painmentioning
confidence: 99%
“…One of the mechanisms of the C8 anticonvulsant properties seems to be mediated through adenosine receptors. It is well established that elevated extracellular adenosine reduces seizure activity in several seizure models, and the anticonvulsant action is mediated through A 1 R adenosine receptors (104,105). One of the main factors controlling the amount of extracellular adenosine is the adenosine kinase (ADK) (105).…”
Section: Differential Effects Of C8 and C10mentioning
confidence: 99%
“…It is well established that elevated extracellular adenosine reduces seizure activity in several seizure models, and the anticonvulsant action is mediated through A 1 R adenosine receptors (104,105). One of the main factors controlling the amount of extracellular adenosine is the adenosine kinase (ADK) (105). KD reduces ADK activity which results in increased extracellular adenosine and suppressed seizure activity (106).…”
Section: Differential Effects Of C8 and C10mentioning
confidence: 99%
See 1 more Smart Citation